TEACHING METHOD IN DELIVERING SPEAKING MATERIAL FOR SENIOR HIGH SCHOOL GRADE - Nurmaliana Sari Siregar (Journal of Maritime and Education (JME), 2023)
Speaking is one way to communicate which ideas and thought as a message orally. This study focused on teaching method that implemented by a teacher while teaching speaking skill in senior high school. The research applied interview and observation method to conduct this study. The finding of this research was the teacher often implement the role play method while delivering speaking material since its really appropriate to the situation class and student interested. Furthermore role play was variety of activities in which students are provided with information presented in role cards that guide them to simulate real world given the freedom to choose the language they use and develop the personalities and the situations as they wish to make the activity enjoyable and successful as much as possible. Clearly, role play has many advantages, such as; acting requires the use of language. Hence learners will develop their ability of communicating and it provides spontaneous use of language during interaction